MENINGKATKAN KEMAMPUAN DIRI PUSTAKAWAN BERBASIS SOFT SKILL DI ERA REVOLUSI INDUSTRI 4.0 - Abidin, Saenal (Jurnal El-Pustaka, 2020)
The 4.0 industrial revolution changed various fields of human life, starting from their mindset, behavior, even their interests. Their tendency towards everything refers to the ease and accuracy of access. Their desire to obtain information easily becomes a top priority. Meanwhile, the library as a source of information is required to strive continually to provide the best service and keep spreading the times. If not, the library will be disrupted in other words will be left by users and they choose sources of information that they think are better and more fun, for example, social media, the internet, etc. In fact, all sources of information do not necessarily guarantee the accuracy of the data and the ability to provide what is desired. Only the issue of convenience will be a top priority. The library should be the main source of information and make other places as supporting sources. This is why the important role of librarians as library organizers needs to recognize the concepts of self-defense and self-development based on soft skills and hard skills. In the 4.0 era, artificial intelligence, the internet of things, cloud computing, will increasingly become the center of technology development. Everything can be automated through super-smart devices. It seems that this will not happen depending on the way we handle and deal with the challenge because humans have a soul while robots do not. The sweet and sincere smile of the librarian will not be able to be replaced by even the smartest machines.